Choroidal Nodules in Ocular Sarcoidosis - Abramowicz, Stéphane; Wassef, Michel; Touhami, Sara (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Ocular sarcoidosis is present in 30-60% of all sarcoidosis patients. Our purpose is to increase awareness of the various presentations of ocular sarcoidosis. Methods: Short image-based clinical case report. Results: We report on a case of ocular sarcoidosis presenting with unilateral choroidal nodules in a middle-aged man. Sarcoid uveitis is generally bilateral and rather symmetrical. However, choroidal nodules are an exception to this rule, as they generally arise unilaterally. Choroidal nodules are highly responsive to oral corticosteroids. When left untreated, they may evolve to chorioretinal atrophy and secondary choroidal neovascularization. Conclusions: Knowledge of this presentation of ocular sarcoidosis can help clinicians optimize treatment outcomes for patients.